A comprehensive mechanistic analysis of silver dissolution with the monoethanolamine-copper-ammonium system and the development of a novel leaching technology. (August 2022) - Cos-Castillo, C.E.; Fuentes-Aceituno, J.C.
Highlights: Massive precipitation of Cu(OH)2 is inhibited depending on the monoethanolamine (MEA) concentration. MEA induces the formation of silver-MEA activated complexes which catalyzes the silver dissolution. It is possible to minimize the consumption of reagents in the MEA-(NH4 )2 SO4 -CuSO4 system. A novel leaching system containing MEA is proposed without the use of cupric ions. High silver recovery is attained at room temperature with the novel MEA system. Abstract: In the present research, the novel system of monoethanolamine-copper-ammonium was electrochemically studied to improve our knowledge of the reaction mechanism of silver dissolution. This paper introduces the effect of varying the concentration of monoethanolamine (MEA), ammonium sulfate, copper sulfate and temperature on the silver leaching kinetics and mechanism. The study has been complemented with thermodynamic analysis, characterization techniques (FESEM-EDS), leaching tests with H2 O2 as oxidizing agent and electrochemical techniques such as Tafel, linear voltammetry and open circuit potential. The results demonstrate that it is possible to dissolve silver inhibiting the Cu(OH)2 precipitation in the system by increasing the concentration of MEA up to 1.5 M. The anodic polarization of silver reveals that an increase in the MEA concentration from 0.05 to 1.5 M, promotes the silver oxidation kinetics, maintaining the concentrations of 0.3 and 0.8 M of CuSO4 and (NH4 )2 SO4, respectively. Furthermore, the Tafel analysis shows that an increase in temperature from 15 to 45 °C minimizes the charge transfer coefficient and increases the silver oxidation kinetics using a leaching solution which avoids the precipitation of copper hydroxide species. The electrochemical results reveal the catalytic role of MEA during the silver dissolution and the possibility to eliminate the use of cupric ions while an energetic condition higher than 0.4 V vs SHE is maintained. In the case of silver sulfide dissolution, the results revealed that the reductive decomposition of silver sulfide is favored at a more cathodic potential than −0.6 V vs SHE with the MEA-Na2 SO4 -(NH4 )2 SO4 system, this cathodic pre-treatment facilitates the accelerated dissolution of silver from Ag2 S using the same MEA leaching system. Finally, it is possible to dissolve 81 % of metallic silver using a conventional batch reactor with the MEA-Na2 SO4 -(NH4 )2 SO4 -H2 O2 novel system at room temperature.